Identification of polymorphisms in TYRP1, DCT and RAB38 genes and their association with coat color in alpacas - Melo-Rojas, Carola; Bravo-Matheus, P. Walter; Amaht Araoz, Cesar; Zapata-Coacalla, Celso (Frontiers in Animal Science, 2023)
The goal of this study was to characterize and investigate the effect of single nucleotide polymorphisms (SNPs) or InDels in tyrosinase related protein 1 (TYRP1), dopachrome tautomerase (DCT), and Rasrelated protein 38 (RAB38) genes on coat color in South American camelids. TYRP1 is among one of the major regulators of pigmentation in mammals. DCT is a pigment cell-specific gene that plays an important role in the melanin synthesis pathway and the expression of skin color. RAB38 is involved in the transport of tyrosinase (TYR) and TYRP1, which are key enzymes in melanin production.Five fleece color tones from 327 alpacas (white, black, brown, gray and light fawn) were investigated to characterize and identify polymorphisms that play a role in coat color. Among the SNPs and Indels identified in the coding region, statistical analysis was performed to determine the association between the polymorphisms and fleece color in camelids, as well as the determination of allelic frequencies.Twenty two polymorphisms in the coding region, seven of them were nonsynonymous, eleven were synonymous, three located in the 5'UTR region and one deletion in the 3'UTR region were identified in the TYRP1 gene; in the DCT gene were identified twenty two polymorphisms, where five of them were non-synonymous, twelve were synonymous, one polymorphism in the 5'UTR region and four in the 3'UTR region; in adition, in the RAB38 gene six polymorphisms were identified, one was nonsynonymous, two were synonymous, in addition to three polymorphisms in the 3'UTR region were found in the RAB38 gene. There were low to moderate polymorphisms in the populations. Significant differences (P<0.001) were found with color fiber in the alpaca populations studied for TYRP1 and DCT genes.